2002
DOI: 10.1002/glia.10095
|View full text |Cite
|
Sign up to set email alerts
|

GM‐CSF and M‐CSF modulate β‐chemokine and HIV‐1 expression in microglia

Abstract: Significant numbers of patients with acquired immunodeficiency syndrome (AIDS) develop CNS infection primarily in macrophages and microglial cells. Therefore, the regulation of human immunodeficiency virus type 1 (HIV-1) infection and activation of the brain mononuclear phagocytes subsequent to infection are important areas of investigation. In the current report, we studied the role of granulocyte-macrophage colony-stimulating factor (GM-CSF) and macrophage-CSF (M-CSF) in the expression of antiviral beta-chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…We previously demonstrated that the CD4 promoter-regulated expression of hu-cycT1 was associated with a marked increase in granulocyte-macrophage colony-stimulating factor (GM-CSF)-induced HIV-1 production by JR-CSF mouse monocytes (69). Inflammatory factors such as LPS induce activated astrocytes to produce GM-CSF, and increased GM-CSF production may play a contributory role in the development of HAD (67). We investigated if the support of Tat responsiveness by the expression of hu-cycT1 also increased HIV production induced by GM-CSF in mouse brains carrying an integrated HIV provirus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the CD4 promoter-regulated expression of hu-cycT1 was associated with a marked increase in granulocyte-macrophage colony-stimulating factor (GM-CSF)-induced HIV-1 production by JR-CSF mouse monocytes (69). Inflammatory factors such as LPS induce activated astrocytes to produce GM-CSF, and increased GM-CSF production may play a contributory role in the development of HAD (67). We investigated if the support of Tat responsiveness by the expression of hu-cycT1 also increased HIV production induced by GM-CSF in mouse brains carrying an integrated HIV provirus.…”
Section: Resultsmentioning
confidence: 99%
“…Activated astrocytes produce GM-CSF in response to inflammatory signals that would activate microglia, stimulate them to proliferate, and trigger the CNS inflammatory response (41). HIVE is associated with increased GM-CSF production in brains that localized predominantly to astrocytes (15,67), and the AIDS dementia complex is associated with elevated levels of GM-CSF in the cerebrospinal fluid (53). Systemic GM-CSF was reported to induce a 10-fold increase in the HIV load in the spinal fluid of a treated patient (38), and GM-CSF has been reported to increase HIV-1 replication in brain tissue explants (32) and primary monocyte/macrophages and monocyte cell lines (19,37,47,60).…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 and IL-10 enhance the entry and replication of HIV-1 in microglia through up-regulation of CD4 and CCR5 expression, respectively (368). The chemokines CCL5/RANTES, CCL3/MIP-1␣, CCL4/MIP-1␤, all of which bind to CCR5, are inhibitory to HIV-1 replication in microglial cells, apparently by their ability to block viral entry (177,327). GM-CSF and macrophage-colony stimulating factor (M-CSF) stimulate the production of these ␤-chemokines but actually inhibit the antiviral properties of these chemokines when added to microglial cell cultures (327).…”
Section: Virusesmentioning
confidence: 99%
“…Human fetal CNS cell cultures were prepared from human fetal abortuses as previously described (20,22,26,27). All procedures were approved by the Albert Einstein College of Medicine institutional review board.…”
Section: Microglial and Thp-1 Cell Culturementioning
confidence: 99%
“…HIV-1 isolates were obtained from the AIDS Repository and propagated in PBMC as previously described (27). Mock infection consisted of exposure to PBMC supernatants without HIV-1.…”
Section: Hiv-1 Exposure Of Microgliamentioning
confidence: 99%